To solve the system of equations:
-9x + y = 12
2x + 4y = -28
We can use the method of substitution or elimination. Let's use the substitution method.
From the first equation, we can rewrite it as y = 9x + 12.
Now let's substitute this value of y into the second equation:
2x + 4(9x + 12) = -28
2x + 36x + 48 = -28
38x + 48 = -28
38x = -28 - 48
38x = -76
x = -76/38
x = -2
Now substitute this x value back into the first equation to find y:
-9(-2) + y = 12
18 + y = 12
y = 12 - 18
y = -6
Therefore, the solution to the system of equations is (x, y) = (-2, -6).
Solve the system of equations.%0D%0A–9x+y=12%0D%0A2x+4y= −28(1 point)%0D%0A(, )
1 answer